2020
DOI: 10.1038/s41560-020-00720-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production via microwave-induced water splitting at low temperature

Abstract: Supplying global energy demand with CO2-free technologies is becoming feasible thanks to the rising affordability of renewable resources. Hydrogen is a promising vector in the decarbonization of energy systems, but more efficient and scalable synthesis is required to enable its widespread deployment. Here we report contactless H2 production via water electrolysis mediated by the microwavetriggered redox activation of solid-state ionic materials at low temperatures (<250 ºC). Water was reduced via reaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 52 publications
0
87
1
Order By: Relevance
“…A few studies on thermochemical redox reactions via microwave heating have been reported. 12,28,29 The studies showed that the direct radiation of microwave can promote the loss of lattice oxygen on metal oxides. The microwave-driven plasma introduced in the current work, however, is positioned far from the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies on thermochemical redox reactions via microwave heating have been reported. 12,28,29 The studies showed that the direct radiation of microwave can promote the loss of lattice oxygen on metal oxides. The microwave-driven plasma introduced in the current work, however, is positioned far from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the absorption of plasmagenerated electrons is expected to facilitate the loss of lattice oxygen and the subsequent re-distribution of electron charge in metal oxides. 12,13 Those rich effects of plasma on both reactants and metal oxide catalysts could reduce the reduction temperature or enhance the reaction kinetics at a given temperature. 8,14 Second, plasma can induce a self-heating effect in the applied catalyst sample, which considerably diminishes the heating demand for the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Charge compensation occurs via oxygen vacancies, which represent the oxygen storage capacity. This redoxactivity is suitable for a wide range of applications, e.g., the electrolyte in solid oxide fuel cells (SOFC), oxygen permeating dense membranes, automotive exhaust control, soot oxidation in the automotive industry, catalyst for steam reforming, water-gas shift, hydrogen production, and oxidation reactions [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…One method towards process intensification is chemical looping, whereby oxidation reactions are decoupled into twostep, spatially separated cyclic redox processes. [20][21][22][23] Chemica l looping is a new frontier for producing valuable chemicals in a clean and efficient manner, [24][25][26][27][28] and has been demonstrated for processing methane, [28][29][30][31][32][33][34][35] biofuels, 36,37 syngas, 38,39 coal and carbonaceous feedstocks 22,40,4 1 with low cost, reduced emissions and higher energy efficiency. Herein, we proposed and validat ed the first chemical looping ammonia oxidation (CLAO) process .…”
mentioning
confidence: 99%